Penggunaan sistem e-visa dalam peningkatan ekonomi berbasis pariwisata : analisis kunjungan turis mancanegara di Bali - Adrian, Marcellino; Resen, Putu Titah Kawitri; Renaningtyas, Maria Agatha (Institute for Advanced Science Social, and Sustainable Future, 2023)
Tourism is a critical need and a fundamental part of today's modern human lifestyle that cannot be separated. Many tourists from European countries choose to travel to Asian countries to gain new experiences and atmosphere. Indonesia itself is one of the countries that is a favorite holiday destination for foreign tourists from Europe, Australia, and several other Asian countries. Bali is one of the areas in Indonesia that many foreign tourists visit. Due to its beauty and unique culture, Bali rightfully deserves to become a Special Economic Zone (KEK) for tourism in Indonesia, a reputation it has long held. Apart from Bali, several other provinces, such as Lombok, NTT, and Jogja, are also planned to become particular tourism areas. However, unfortunately, the COVID-19 pandemic, which entered Indonesia at the beginning of March 2020, significantly reduced the number of foreign tourist visits to Bali. The year before the pandemic had seen 456,218 tourist visits, but the implementation of PSBB and the closure of entry and exit points to Indonesia at both ports caused a drastic drop. And airport. However, in 2023, when the pandemic is over, coupled with geopolitical turmoil in several parts of the world, Indonesian tourism will recover quickly and again become a favorite for foreign tourists to visit, one of which is tourists from Russia, whose numbers currently dominate in Bali. The method used in collecting data for this journal is a qualitative method. Data is collected directly at the Denpasar Immigration Office to determine the number of foreign tourist visits and their violations, especially for Russian tourists who have recently committed many violations in Bali. The discussion in this journal will focus on implementing the Evisa system, which is a breath of fresh air for the revival of Bali tourism after the pandemic. Apart from that, this journal will highlight case studies of the number of Russian tourists visiting Bali and the violations committed, supported by data from the Denpasar Immigration office. This journal hopes to increase awareness by strengthening regulations for foreign tourists in Indonesia to create a good tourism ecosystem.